Safety Usage of Encapsulated Mineral Fertilizers Based on Polymeric Waste - Oleg Nagurskyy (Polish Society of Ecological Engineering (PTIE), 2022)
The research was conducted on growth and vital functions of watercress in the conditions of encapsulated mineral fertilizers treatment. The cyclic application of mineral fertilizers during three vegetation periods is simulated in this paper. Used mineral fertilizers are encapsulated on the basis of polyethylene terephthalate and polystyrene waste. It was found that the intermediate products of the polymer covering decomposition do not have a negative impact on the soil environment and the use of encapsulated fertilizers is safe for plants growing.